Respon Investor atas Tanggung Jawab Sosial Tata Kelola Perusahaan di Indonesia: Perspektif Resource Based View - Firmansyah, Amrie; Febrian, Wahyudi; Jadi, Pramuji Handra; Husna, Mitsalina Choirun; Putri, Maritsa Agasta (E-Jurnal Akuntansi; Vol 31 No 8 (2021)DO - 10.24843/EJA.2021.v31.i08.p04, 2021)
This study aims to examine the effect of corporate social responsibility disclosure and corporate governance disclosure on firm value in Indonesia. This study uses a Resource Based View perspective which is still rarely used in testing firm value. This study uses data and information from manufacturing companies listed on the IDX from 2016 to 2019. After purposive sampling, the final sample that can be used is 260 observations. Testing the data using multiple linear analysis with panel data. The test results show that corporate social responsibility and corporate governance have no effect on firm value. The test results in this study indicate that the Financial Services Authority as the supervisor of issuers in the Indonesian capital market, needs to improve corporate governance and corporate social responsibility arrangements. Keywords: Governance; Sustainability; Disclosure; Firm Value.